TINGKAT KEBERHASILAN PERPINDAHAN KOLONI Trigona spp. PADA SARANG BUATAN DI HUTAN LARANGAN ADAT DESA RUMBIO KABUPATEN KAMPAR - Asprizatul Azlan; Defri Yoza; M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Trigona spp. is include into stingless bee honey. Trigona spp. has another names, such as, galo-galo (Sumatera), klanceng, lenceng (Jawa), andteuweul (Sunda). The population of Trigona spp. in many areas in indonesia. Trigona spp. produce are honey, pollen, royal jelly, propolis and beeswax. People do not know much yet about the benefit and how to cultivation of Trigona spp. type, material and size of bee’s nest. The purpose of this research is to know successfull affectiveness movement of Trigona spp. in type, material and size of artificial nest. This research used two method, survey and experiment. The first survey got 19 bee’s nest of Trigona spp. in 7 trees. In the next experiment, the resercher tried to test 6 artificial nests (2 bee’s nest made by half of a coconut shell, 2 bee’s nest made by bamboo and 2 bee’s nest made by wooden box) and the different size of box. The experiment of 6 artificial nests was a theory of eduction/attachment. The artificial nest affixed to red chelate tree (Syzygium sp.), kempas (Koompassia malaccensis), jackfruit (Artocarpus heterophyllus) and red chelate tree was moudly/dead. The result of this research show that type of Trigona spp. that lifeatThe Prohibition Forest of Indigenous Village of Rumbio Kampar Regency. There are three kinds : Trigona collina, Trigona incica andTrigona terminata. The preferred and ideal artificial nest of Trigona spp. was wooden box 3 segment in Ttot = 65 cm, basic segment T1 =30 cm, middle segment T2 =25 cm andtop segment T3 = 10 cm.Key words:Trigona spp., The Prohibition Indigenous Forest, artificial nests